ANALISIS PENGGUNAAN APLIKASI MANPRO PADA LIFE CYCLE PROYEK KONSTRUKSI - yani, Mirna (Fakultas Teknik, Universitas Wiraraja, 2024)
In the present digital era, it is essential to use technological assistance at every stage of any activity. One such tool in project management is the Manpro application. In the Grange Park Fatmawati – Apartment and Facilities project, PT Erakencana Tunggal, as the project owner, utilizes the Manpro application as a communication platform to coordinate and monitor work online. The Manpro application helps construction actors in supervising projects by reducing communication barriers and increasing project visibility through online reporting, thus enhancing project efficiency and productivity. The research uses a quantitative approach and the Pairwise Comparison method to calculate the weight of using the Manpro application at each stage of the project life cycle, feasibility, and user satisfaction. The results show that the largest weight of using the Manpro application is at the supervision and control stage, with a weight of 28.2%. The feasibility value of the Manpro application at all stages of the project life cycle is 84%, indicating that it is very feasible. The level of owner satisfaction in using this application is in the satisfied criteria, with a value of 83.09%.